Kinetic study of the OH, NO3 radicals and Cl atom initiated atmospheric photo-oxidation of iso-propenyl methyl ether. (February 2016) - Taccone, Raúl Alberto; Moreno, Alberto; Colmenar, Inmaculada; Salgado, Sagrario; Martín, María Pilar; Cabañas, Beatriz
Abstract: Rate coefficients at room temperature and atmospheric pressure for the reaction of isopropenyl methyl ether ( i -PME) (CH2 C(CH3 )OCH3 ), with OH and NO3 radicals and with Cl atoms have been determined in a 50 L Pyrex glass reaction chamber in conjunction with Fourier Transform Infrared absorption spectroscopy (FTIR) as a detection technique. The chamber is equipped with a White-type multiple-reflection mirror system with a total optical path length of ≈200 m. Additional experiments were carried out using evacuable Teflon-coated bags (volume 150 L) and a gas chromatography/mass spectrometry-time of flight (GC-TOF MS) detection system. This is the first kinetic study carried out to date for these reactions. The rate coefficients k (in units of cm 3 molecule −1 s −1 ) obtained are: (1.14 ± 0.10) × 10 −10 for the OH reaction, (2.41 ± 0.50) × 10 −11, for the NO3 reaction and (7.03 ± 0.67) × 10 −10 for the Cl reaction. A mechanism is proposed from the observed reaction products. The atmospheric lifetimes of the studied ether is estimated considering the rate coefficients of the reactions with OH and NO3 radicals and Cl atom. Calculated atmospheric lifetimes reveal that the dominant loss process for i -PME is clearly the night-time reaction with the NO3 radical. The radiative efficiency (RE) is obtained from the infrared spectra of the ether and the global warming potential (GWP) is then estimated. Atmospheric implications of the ether emission are discussed. Graphical abstract: IR spectra of the detected products in the reaction of i -PME with NO3 radicals. a) Spectrum of i -PME at t = 0 min; products reaction at b) t = 10 min and c) t = 20 min; library spectra for d) methyl acetate and e) formaldehyde. Highlights: Rate coefficients obtained for reaction of CH2 C(CH3 )OCH3 with atmospheric oxidants. It is proposed a possible mechanism from the observed products. Different atmospheric implications are considered.